2022
DOI: 10.1186/s13293-022-00463-x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational hypoxia in late pregnancy differentially programs subcortical brain maturation in male and female rat offspring

Abstract: Background Hypoxia is associated with pregnancy complications, such as preeclampsia, placental abruption, and gestational sleep apnea. Hypoxic insults during gestation can impact the brain maturation of cortical and subcortical pathways, such as the nigrostriatal pathway. However, the long-term effects of in utero hypoxic stress exposure on brain maturation in offspring are unclear, especially exposure during late gestation. The purpose of this study was to determine the impact of gestational h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 124 publications
1
12
0
Order By: Relevance
“…To examine the impact of sex on OSA-associated symptoms (inflammation, OS, memory, motor, anxiety, compulsivity), we utilized an experimental rat model of OSA called chronic intermittent hypoxia (CIH). CIH exposure replicates the fragmented episodes of hypoxia observed in OSA [ 52 ]. Further, to examine the mechanisms of mtOS on sex differences in CIH, we implanted osmotic pumps subcutaneously in a subgroup of rats to continuously administer a mitochondria-targeting superoxide dismutase mimetic, MitoTEMPOL (MT), to block mtOS.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations
“…To examine the impact of sex on OSA-associated symptoms (inflammation, OS, memory, motor, anxiety, compulsivity), we utilized an experimental rat model of OSA called chronic intermittent hypoxia (CIH). CIH exposure replicates the fragmented episodes of hypoxia observed in OSA [ 52 ]. Further, to examine the mechanisms of mtOS on sex differences in CIH, we implanted osmotic pumps subcutaneously in a subgroup of rats to continuously administer a mitochondria-targeting superoxide dismutase mimetic, MitoTEMPOL (MT), to block mtOS.…”
Section: Introductionmentioning
confidence: 86%
“…During their sleep phase of the circadian cycle, CIH was performed for 8 h starting at 21:00. The CIH protocol consisted of intermittent oxygen reduction from 21% (room air) to 10% in 6-min cycles per hour (i.e., 10 cycles/h) over 8 h/day for a period of 14 days, as previously described [ 6 , 52 , 78 , 79 ]. 10 CIH cycles per hour results in an apnea–hypopnea index (AHI) of 10, which is consistent with mild sleep apnea in humans [ 31 , 79 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of hypoxia on the brain’s development and function is also manifested in an age-dependent manner. Abundant evidence has shown that hypoxia exposure causes neurodevelopmental deficits in rats ( Moromisato et al, 1996 ; Wilson et al, 2022 ) and infants ( Wang et al, 2018 ; Dassios et al, 2022 ; Plomgaard et al, 2022 ) at prenatal and perinatal stages, contributes to brain myelin injury in adult mice ( Chen et al, 2021 ) and brain white matter injury in adult human ( Muttikkal and Wintermark, 2013 ), and exacerbates memory impairment in aging mice ( Sun et al, 2006 ) and human ( Park et al, 2013 ). However, few studies have addressed the impact of hypoxia on adolescents, especially brain functions during this developmental stage.…”
Section: Introductionmentioning
confidence: 99%